2018
DOI: 10.3390/membranes8040132
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Pressure Dependence of Gas Permeation in a Microporous Tröger’s Base Polymer

Abstract: Gas transport properties of PIM-EA(H2)-TB, a microporous Tröger’s base polymer, were systematically studied over a range of pressure and temperature. Permeability coefficients of pure CO2, N2, CH4 and H2 were determined for upstream pressures up to 20 bar and temperatures up to 200 °C. PIM-EA(H2)-TB exhibited high permeability coefficients in absence of plasticization phenomena. The permeability coefficient of N2, CH4 and H2 increased with increasing temperature while CO2 permeability decreased with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 25 publications
4
29
0
Order By: Relevance
“…In terms of gas permeability, it is easier for the gas to pass through an amorphous structure due to the absence of diffusion limitation. This was also confirmed by noticing an increase in the membrane permeability for longer chain polymers [69]. Table 4 summarizes the mentioned studies for membrane analysis by XRD.…”
Section: Data Interpretationsupporting
confidence: 54%
“…In terms of gas permeability, it is easier for the gas to pass through an amorphous structure due to the absence of diffusion limitation. This was also confirmed by noticing an increase in the membrane permeability for longer chain polymers [69]. Table 4 summarizes the mentioned studies for membrane analysis by XRD.…”
Section: Data Interpretationsupporting
confidence: 54%
“…On the other hand, the selectivity slightly changes with the increase in pressure. Lasseuguette et al studied the impact of pressure on gas permeation properties and found the same result in case of newly fabricated membranes (PIM‐EA(H 2 )‐TB).…”
Section: Factors Affecting the Membrane Separationmentioning
confidence: 61%
“…Lasseuguette et al studied the influence of temperature on the membrane permeability using a PIM‐EA(H 2 )‐TB membrane. Results showed that an increase in membrane permeability was observed in case of CH 4 , H 2 , and N 2 .…”
Section: Factors Affecting the Membrane Separationmentioning
confidence: 99%
“…As observed in Figure 8 and Figure 9 , the CO 2 permeability and CH 4 permeability decreased when the pressure difference increased from 5 to 7 bar. This is a common behavior of glassy polymers [ 31 , 32 ]. Biondo et al [ 33 ] reported a decrease in CO 2 permeability when the pressure increased for PSF and it was explained that the behavior was typical for a dual-mode model.…”
Section: Resultsmentioning
confidence: 99%